A comparison principle for higher order nonlinear hypoelliptic heat operators on graded Lie groups. (February 2022) - Ruzhansky, Michael; Yessirkegenov, Nurgissa
Abstract: In this paper we present a comparison principle for higher order nonlinear hypoelliptic heat operators on graded Lie groups. Moreover, using the comparison principle we obtain blow-up type results and global in t -boundedness of solutions of nonlinear equations for the heat p -sub-Laplacian on stratified Lie groups.